Identification of Mycobacterium avium Genotypes with Distinctive Traits by Combination of IS1245-Based Restriction Fragment Length Polymorphism and Restriction Analysis of hsp65 - Oliveira, R. S. (American Society for Microbiology, 2003)
One-hundred eight Mycobacterium avium isolates from pigs, humans, birds, and bovines were typed by the IS1245-based restriction fragment length polymorphism (RFLP) method and PCR-restriction enzyme analysis (PRA) of hsp65. Nine clusters of isolates showing more than 80% similarity in their RFLP profiles were detected. The largest cluster (cluster B) included 32 of 79 pig isolates (40.5%), 3 of 25 human isolates (12%), and 1 of 2 bovine isolates, comprising 33% of all isolates. The second largest cluster (cluster A) included 18 pig isolates (22.8%) and 6 human isolates (24%). Six smaller clusters included six pig isolates (clusters C and D), four and two human isolates (clusters E and F, respectively), two pig isolates (cluster I), and two pig isolates plus one bovine isolate and the avian purified protein derivative strain (cluster H). Cluster G represented the “bird-type” profile and included the bird isolate in this series, one pig isolate, plus reference strain R13. PRA revealed four allelic variants. Seventy-seven isolates were identified as M. avium PRA variant I, 24 were identified as M. avium PRA variant II, 6 were identified as M. avium PRA variant III, and 1 was identified as M. avium PRA variant IV. Except for three isolates from cluster B, each of the RFLP clusters was associated with a single PRA pattern. Isolates with unique (nonclustered) RFLP profiles were distributed between PRA variants I and II, and there was one unique isolate of PRA variant IV. These observations are consistent with divergent evolution within M. avium, resulting in the emergence of distinct lineages with particular competence to infect animals and humans.